Penyusunan laporan keuangan berbasis ISAK 35 menggunakan Aplikasi MYOB pada Masjid Al Khautsar - Saleh, Fadly Febrianto; Afandi, Dhullo; Kalalo , Meily Y. B. (Yayasan Widyantara Nawasena Raharja, 2025)
In non-profit-oriented entities, the main purpose of preparing a financial statement according to the Interpretation of Financial Accounting Standards (ISAK) No. 35 is to provide relevant information to meet the interests of donors, organization members, creditors, and other parties that provide resources for nonprofit organizations. Additionally, the utilization of recording applications can assist in preparing the financial statements of an entity. The aim of this research is to produce a financial statement recording concept based on ISAK 35 using the MYOB application at Al Khautsar Mosque. The type of research used is qualitative research with a descriptive approach. The results obtained indicated that the MYOB application could not generate financial statements based on ISAK 35 at Al Khautsar Mosque